Implementation of Indigenous Knowledge-Laden Leaflets on Student Learning Outcomes on Global Warming Materials - Rani, Putri Oktafia; Hariyatmi, H (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2024)
This study aims to examine the Implementation of Indigenous Knowledge-Laden Leaflets on Student Learning Outcomes on Global Warming Material. This study used a quasi-experimental method with a Nonequivalent control group design. This study used classes XA, XD, XE and XF, each class consisting of 36 students. In the class there is a selection of criteria, for class XA with high class criteria, class XD with medium class criteria, class XE with low class criteria, and class XF as a control class (Biology Teacher document). The research instrument is in the form of cognitive, affective, and psychomotor results. Data analysis of learning outcomes using one way anova test with normality test and homogeneity test. The results of the calculation of learning outcomes with one way anova test obtained a significance value (2-tailed) of (0.000) < (0.050) then the null hypothesis (H0) is rejected. And then the further test obtained a significance probability value of (0.917) > (0.050), therefore (H0) is accepted. This means that the treatment has an effect on student learning outcomes and the results of further tests have no effect on the learning outcomes of experimental classes (high, medium, and low clas).